Exploring the Solar System: from mapping to prospecting - Fabrizio Bernardini (mediaGEO soc. coop., 2019)
Solar System exploration is changing, opening the field to prospectors and then miners. This is a process we have already seen many times on our planet and for the first time in human history, we are witnessing the revolution that holds the keys to a new frontier.